Relevansi Maqashid Al-Syariah Jasser Auda Terhadap Pemberdayaan Ekonomi Umat Di Era Kontemporer - Isni Setyani (CV. ITTC INDONESIA, 2025)
This study examines the relevance of Maqashid al-Syari'ah Jasser Auda's thinking in the context of the economic empowerment of the ummah in the contemporary era. Jasser Auda offers a systemic approach to maqashid that is more comprehensive than the classical approach, emphasizing holistic dimensions, openness, interconnectedness and multidimensionality. This study uses a qualitative method with a descriptive-analytical approach through literature studies. The results of the study show that Jasser Auda's maqashid approach is very relevant to overcome the complexity of contemporary economic problems, such as structural poverty, economic inequality, and digital economic challenges. The concept of empowerment in maqashid includes economic, political, and psychological dimensions. In the economic dimension, empowerment means providing access to capital, markets, technology, and knowledge. In the social dimension, empowerment means strengthening social networks and social capital that support economic activities. In the political dimension, empowerment means giving a voice and participation in economic decision-making. In the psychological dimension, empowerment means building self-confidence and self-efficacy.